P155 Compliance With Guidelines For The Management Of Theophylline In Patients With Acute Exacerbations Of Copd. (10th November 2014) - Ullah, M; Anshur, D; Lugg, S; Gompertz, S
Abstract : Introduction: Theophylline therapy has a role in COPD patients who fail to respond adequately to inhaled bronchodilators and show symptomatic benefit from a trial of the drug. Treatment is complicated by drug interactions and its narrow therapeutic range (10–20 mg/L). High serum levels increase the risk of toxicity, demonstrating numerous symptoms such as nausea, vomiting, headaches, dyspepsia, insomnia and behavioural disturbances. Serious adverse effects such as cardiac arrhythmias and epileptic seizures tend to occur at serum levels above this reference range. NICE guidelines for COPD state that a theophylline level should be measured on admission in patients admitted for acute exacerbation of COPD (AE-COPD). 1 The aim of this study was to audit compliance with these guidelines. Methods: Patients with a diagnosis of AE-COPD were retrospectively analysed over a 6-month period (June–December 2013) at a university hospital. Those who were prescribed theophylline within 24 h of admission were included in the study. Further information was gathered including theophylline level, date of request, and subsequent dose adjustment. Paper and computerised medical and prescribing records were reviewed using a set pro-forma. Results: Of a total of 54 patients in the study, 23 patients (43%) had theophylline levels checked during their hospital admission. Only 5 (9%) patients had theophylline levels within 24 h of admission, with the mean number of days from admission to assessment being 4.69 (SD+ 5.29). Of those patients, 13 patients (56.5%) had a level within subtherapeutic range (<10 mg/L), and 8 patients (61%) receiving subsequent dose adjustment. There were no patients found to have a theophylline level above therapeutic range (>20 mg/l). Conclusion: Improvement is needed in compliance with guidelines for the theophylline monitoring in patients with AE-COPD, as more than half of patients did not have levels checked during their hospital admission. Furthermore, dose adjustments were made in only 2 of 3 patients. Changes can be implemented through education to junior doctors, implementation of electronic prescribing alerts, and adding this to our MDT COPD bundle checklist. Further prospective audit cycle will be performed to assess improvements. Reference: NICE Guidelines [CG101]2010